2020
DOI: 10.3389/fpsyg.2020.573291
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Hangover May Affect Cognitive Research

Abstract: University students are the most employed category of participants in cognitive research. However, researchers cannot fully control what their participants do the night before the experiments (e.g., consumption of alcohol) and, unless the experiment specifically concerns the effects of alcohol consumption, they often do not ask about it. Despite previous studies demonstrating that alcohol consumption leads to decrements in next-day cognitive abilities, the potential confounding effect of hangover on the validi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
(43 reference statements)
2
15
1
Order By: Relevance
“…All of them received academic credits for their participation to the experiment. Before starting the experiment, all participants completed a questionnaire in which they reported their handedness, any vision or hearing impairment, and whether their psychophysiological state was affected by alcohol consumption or insufficient sleep in the last 24 h. One participant was left-handed; all of them reported to have normal hearing, normal or corrected to normal vision and that their psychophysiological state was not affected by alcohol consumption or insufficient sleep in the last 24 h 38 . All participants of this study signed a written informed consent before the beginning of the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…All of them received academic credits for their participation to the experiment. Before starting the experiment, all participants completed a questionnaire in which they reported their handedness, any vision or hearing impairment, and whether their psychophysiological state was affected by alcohol consumption or insufficient sleep in the last 24 h. One participant was left-handed; all of them reported to have normal hearing, normal or corrected to normal vision and that their psychophysiological state was not affected by alcohol consumption or insufficient sleep in the last 24 h 38 . All participants of this study signed a written informed consent before the beginning of the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…They were all used to the left-to-right writing direction and were naive about the purpose of the study. All participants reported that their psychophysiological state was not affected by alcohol consumption or insufficient sleep in the last 24 hr (Murgia et al, 2020). Written informed consent was obtained before participation; the experiment was conducted in accordance with the ethical standards established by the Declaration of Helsinki and with the agreement of the University of Trieste Ethics Committee.…”
Section: Participantsmentioning
confidence: 99%
“…Like in Experiment 1, the sample size was determined using the same power analyses as for Experiment 1, and following the suggestions by Cipora and Wood (2017), we therefore recruited a number of participants considered “large” for this type of study. All participants reported that their psychophysiological state was not affected by alcohol consumption or insufficient sleep in the last 24 hr (Murgia et al, 2020).…”
Section: Experiments 2a and 2bmentioning
confidence: 99%
“…Magnitude classification is considered a “direct task”, because it requires participants to directly compare a feature of the stimuli relevant for the study (i.e., magnitude) with a reference. Conversely, parity judgement is considered an “indirect task”, because participants are asked to judge a feature of the stimuli irrelevant to the study, namely parity (Mingolo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%